On the origin of white dwarfs with carbon-dominated atmospheres: The case of H1504+65 - Althaus, Leandro Gabriel (2009)
Aims. We explore different evolutionary scenarios to explain the helium, deficiency observed, in H1504+65, the most massive known PG1159 star. Methods. We concentrate mainly on the possibility that this star could be the result of mass loss shortly after its born-again and during its subsequent evolution through the [WCL] stage. This possibility is consistent with observational evidence of extensive mass-loss events in Sakurai's object and is in line with the finding that these mass losses give rise to PG1159 models with thin heliumrich envelopes and high rates of period change, as demanded by the pulsating star PG1159-035. We compute the post-born-again evolution of massive sequences by taking into account different mass-loss rate histories. Results. Our results show that stationary winds during the post-born-again evolution fail to remove completely the helium-rich envelope and are therefore unable to explain the helium deficiency observed, in H1504+65. Stationary winds during the Sakurai and [WCL] stages remove at most half of the envelope that survives the violent hydrogen burning during the born-again phase. Conclusions. In view of our results, the proposed evolutionary sequence of born-again stars to H.1504+65 and then to white dwarfs with carbon-rich atmospheres is difficult to reproduce unless the entire helium-rich envelope is ejected by non-stationary mass-loss episodes during the Sakurai stage.